The United Fruit Company's tourist business and the creation of the "Golden Caribbean", 1899-1940. (16th May 2016) - Martin, James W.
Abstract : Purpose: This paper aims to examine the tourist business and marketing strategies of a US agribusiness giant, the United Fruit Company (UFCO), between its incorporation in 1899 and 1940. It considers how tourist marketing served the company's public-relations interest and tourism's broader connection to narratives of US ascendancy in the Caribbean Basin. Design/methodology/approach: This study is based on original research in a series of published company materials, including annual reports and a wide variety of marketing materials, as well as a variety of rare primary sources documenting the experiences of US tourists on UFCO cruises. Findings: From its incorporation in 1899, the UFCO developed a Caribbean cruise business as a vital part of its strategies of vertical integration and expansion around the region. Marketing tropical travel at a time when tropical disease dominated US perceptions of such places required a thorough conceptual makeover, and UFCO publicity played an important part in this process. The company advertised Caribbean destinations first for their therapeutic possibilities, but by the 1920s, a framework of anachronistic space and picturesque primitivism predominated in marketing campaigns. The structure of this narrative naturalized the company's, and more broadly, US, hegemony in the region. While on cruises, tourists became witnesses to and participants in a series of spectacles and activities highlighting the company's technological prowess and benevolence. Originality/value: This analysis centers on a largely overlooked dimension of the famed banana company's enterprise. It is grounded in a wide collection of primary sources largely untapped by researchers, a source base that brings tourist perception and experience into the story of this company's marketing efforts. This research brings tourism and leisure into the historical discussion of US power in early-twentieth-century Latin America.